Timon of Athens - "Shakespeare, William" (Sweet cherry publishing: China, 2013)
Shakespeare's Timon of Athens is the tale of a rich Athenian who lived a lavish life, spending his wealth on his friends. Eventually, when his wealth ceases and he asks his friends for help, Timon is shocked to find that none of them are prepared to do so. This fills him with hatred for humanity, and he goes on to live the life of a hermit
Keywords: Adaptations Literation